Optimisation of Charcoal and Sago (Metroxylon sagu) Bark Ash to Improve Phosphorus Availability in Acidic Soils - Johan, Prisca Divra; Ahmed, Osumanu Haruna; Maru, Ali; Omar, Latifah; Hasbullah, Nur Aainaa (MDPI AG, 2021)
Soil acidity is an important soil factor affecting crop growth and development. This ultimately limits crop productivity and the profitability of farmers. Soil acidity increases the toxicity of Al, Fe, H, and Mn. The abundance of Al and Fe ions in weathered soils has been implicated in P fixation. To date, limited research has attempted to unravel the use of charcoal with the incorporation of sago (Metroxylon sagu) bark ash to reduce P fixation. Therefore, an incubation study was conducted in the Soil Science Laboratory of Universiti Putra Malaysia Bintulu Sarawak Campus, Malaysia for 90 days to determine the optimum amounts of charcoal and sago bark ash that could be used to improve the P availability of a mineral acidic soil. Charcoal and sago bark ash rates varied by 25%, whereas Egypt rock phosphate (ERP) rate was fixed at 100% of the recommendation rate. Soil available P was determined using the Mehlich 1 method, soil total P was extracted using the aqua regia method, and inorganic P was fractionated using the sequential extraction method based on its relative solubility. Other selected soil chemical properties were determined using standard procedures. The results reveal that co-application of charcoal, regardless of rate, substantially increased soil total carbon. In addition, application of 75% sago bark ash increased soil pH and at the same time, it reduced exchangeable acidity, Al3+, and Fe2+. Additionally, amending acidic soils with both charcoal and sago bark ash positively enhanced the availability of K, Ca, Mg, and Na. Although there was no significant improvement in soil Mehlich-P with or without charcoal and sago bark ash, the application of these amendments altered inorganic P fractions in the soil. Calcium-bound phosphorus was more pronounced compared with Al-P and Fe-P for the soil with ERP, charcoal, and sago bark ash. The findings of this study suggest that as soil pH decreases, P fixation by Al and Fe can be minimised using charcoal and sago bark ash. This is because of the alkalinity of sago bark ash and the high affinity of charcoal for Al and Fe ions to impede Al and Fe hydrolysis to produce more H+. Thus, the optimum rates of charcoal and sago bark ash to increase P availability are 75% sago bark ash with 75%, 50%, and 25% charcoal because these rates significantly reduced soil exchangeable acidity, Al3+, and Fe2+.